2008
DOI: 10.1007/s10526-008-9168-7
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Fusarium wilt of watermelon by a bio-organic fertilizer containing combinations of antagonistic microorganisms

Abstract: Fusarium wilt of watermelon commonly occurs in locations where the crop has been grown for many seasons. Its occurrence results in a severely decreased watermelon crop. The goal of this study was to assess the capability of a new product (bio-organic fertilizer) to control the wilt in Fusarium-infested soil. Pot experiments were conducted under growth chamber and greenhouse conditions. The results showed that the fertilizer controlled the wilt disease. Compared with control pots, the incidence rates of Fusariu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
55
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 42 publications
6
55
0
2
Order By: Relevance
“…Domínguez et al (2008) reported that banana wilt disease caused unfavorable soil conditions such as low pH, electrical conductivity, organic matter, soil fertility and high soil compaction. Wu et al (2009) also observed that soil enzymes activities, soil respiration and microbial biomass were significantly lower in watermelon wilt diseased area compared to un-diseased area. Complex infection caused by plant parasitic nematodes and FOC gave rise to a necrotic and reduced root system, which in turn, resulted in a reduction in the uptake and transportation of water and nutrients by the plant (Poornima et al, 2007).…”
Section: Introductionmentioning
confidence: 70%
“…Domínguez et al (2008) reported that banana wilt disease caused unfavorable soil conditions such as low pH, electrical conductivity, organic matter, soil fertility and high soil compaction. Wu et al (2009) also observed that soil enzymes activities, soil respiration and microbial biomass were significantly lower in watermelon wilt diseased area compared to un-diseased area. Complex infection caused by plant parasitic nematodes and FOC gave rise to a necrotic and reduced root system, which in turn, resulted in a reduction in the uptake and transportation of water and nutrients by the plant (Poornima et al, 2007).…”
Section: Introductionmentioning
confidence: 70%
“…All the biocontrol treatments are at par with the chemical fungicide. Wu et al (2009) reported that a bio-organic fertilizer containing Paenibacillus polymyxa and Trichoderma harzianum reduced Fusarium wilt of watermelon. Role of elevated activities of defense related enzymes as a result of systemic acquired resistance was attributed as mechanism of action for this disease suppression activity.…”
Section: Discussionmentioning
confidence: 99%
“…Antagonists (Fravel et al, 2005) as well as compost amendments (Boulter-Bitzer et al, 2006) have been used but with inconsistent results. Several organisms such as Penicillium oxalicum (De Cal et al, 2009), Paenibacillus polymyxa (Wu et al, 2009), Pseudomonas fluorescens, P. chlororaphis (Tziros et al, 2007) and species of Trichoderma (Pandey and Gupta, 2012) have been evaluated for Fusarium wilt suppression. Trichoderma species are soil inhabitants, competitive saprophytes, and facultative mycoparasites that can colonize the soil and rhizosphere (Harman et al, 2004).…”
mentioning
confidence: 99%
“…In our research it was shown that as fertilizer volume increases, the number of V. dahliae gradually reduced and all treatments showed a significant change in high, medium, and low organic matter content of the soils. This may be due to a direct inhibitory effect or the physiological and biochemical role of antagonist (Wu et al, 2009). It may be due to the organic matter addition to soil improved the microbial activity of original antagonist, thereby reduced the density of soil pathogens, inhibited activities of soil pathogen and reduced the incidence of disease (Ouhdouch, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Although microbial organic fertilizer was less efficient than chemical pesticides; it was clearly a better choice from the perspective of the safety of national agricultural products. Efficiency to control soil-borne disease of other microorganic fertilizer could reach more than 80% by improving the micro-organic fertilizer formulation and production process and optimization of application method (Yogev et al, 2009;Wu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%